Striatal cell-type–specific molecular signatures reveal potential therapeutic targets in a model of dystonia - Kaitlyn M. Roman; Ashok R. Dinasarapu; Suraj Cherian; Xueliang Fan; Yuping Donsante; Nivetha Aravind; C. Savio Chan; H.A. Jinnah; Ellen J. Hess (Neurobiology of Disease)
Abnormal dopamine neurotransmission and striatal dysfunction is implicated in many forms of dystonia, yet the underlying molecular processes remain unknown. Here, we identified thousands of dysregulated genes within striatal spiny projection neuron (SPN) subtypes in a genetic mouse model of DOPA-responsive dystonia (DRD), which is caused by gene defects that reduce dopamine neurotransmission. Although changes in mRNA expression were unique to each SPN subtype, abnormal glutamatergic signaling was implicated in each SPN subtype. Indeed, both AMPA and NMDA receptor-mediated currents were enhanced in direct SPNs but diminished in indirect SPNs in DRD mice. The pattern of mRNA dysregulation was distinct from parkinsonism where the dopamine deficit occurs in adults, suggesting that the phenotypic outcome is dependent on both the timing of the dopaminergic deficit and the SPN-specific adaptions. By leveraging these disease-specific molecular signatures, we identified LRRK2 inhibition, among other mechanisms, as a novel therapeutic target for dystonia.